Prinsip Pengakuan dalam Pembentukan Negara Baru Ditinjau dari Hukum Internasional (Lex Jurnalica, 2011)
The birth of a new nation in the international community would elicit a reaction from the country - other countries are reflected in the statement - a statement accepting or acknowledging the birth of a new country or vice versa there are countries - countries that reject or do not recognize the presence of the new state. In recognition of international law is a fairly complicated issue, because it involves the issue of Law and Political issues. Issues to be discussed is the role of the recognition How-world countries in the establishment of a new country? This study is expected to be useful and provide an evaluation of work so that these results can contribute to the development of mind, knowledge of International Law, particularly in terms of recognition of new States, and is also expected to be useful in taking the attitude that relates to the independence of a new State. This study uses a type of normative descriptive study using data types of library materials which are secondary data, ie data - data obtained from reading materials and libraries.Keywords: New Nation, Recognition, International Law